PERBANDINGAN PERTUMBUHAN PASCASAPIH SAPI BRAHMAN CROSS DI DESA WAWASAN DAN DESA PURWODADI DALAM, KECAMATAN TANJUNGSARI, KABUPATEN LAMPUNG SELATAN - Arif Riyanto; Ali Husni; Akhmad Dakhlan; Arif Qisthon (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2021)
This study was conducted with the aim to compare weaning weight, yearling weights, post weaning weight gain up to one year of age and average daily gain (ADG) from weaning to one year of age of Brahman Cross cattle between in Wawasan and in Purwodadi Dalam Villages, Tanjungsari District, Lampung Selatan Regency. The study was conducted in August 2020 in Wawasan Village and Purwodadi Dalam Village, Tanjungsari District, Lampung Selatan Regency, Lampung Province. The data used were secondary data taken from the records of 30 Brahman Cross cattle from each village. A Survey method was used in this research. The sampling was done by using purposive sampling. The variables observed included recording calves birth date, birth weight, weaning date, calf weaning weight, weaning age, and yearling weight. The results of this study indicated that the weaning weight in Wawasan Village (167,39±40,59 kg) and in Purwodadi Dalam Village (161,12±33,39 kg) was not different significantly (P>0.05). Yearling weight of cattle in Wawasan Village (217,41±41,68 kg) and in Purwodadi Dalam Village (202,62±33,86 kg) was not significantly different (P>0.05). Post weaning weight gain to one year of age in Wawasan Village (49,86±15,05 kg) and in Purwodadi Dalam Village (41,49±9,97 kg) was significantly different (P<0.05). Average daily gain from weaning to one year of age in Wawasan Village which reached 0.31±0.09 kg and in Purwodadi Dalam Village which reached 0.26 ± 0.06 kg was significantly different (P<0.05). Keywords : Body weight gain, Brahman cross cattle, Yearling weight, Weaning weight